PEMBANGUNAN SISTEM E-SPD PADA PT. SERASI AUTORAYA - Kuncoro, Siswo; Septiana, Laila; Satriadi, Irawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Serasi Autoraya in its office activities require Travel Service Orders (SPPD), which is a letter of introduction made when the employee will travel to a certain city service. In the making is still using the Microsoft Word and Microsoft Excel applications which must be edited every time a travel trip. In addition SPPD makers must search for data of each employee who will travel on a Microsoft Excel trip. In the manufacture of SPPD that there are currently encountered many shortcomings that must be faced as the occurrence of typing errors in input data so that the manufacture of SPPD done repeatedly. This results in a large amount of paper being wasted, otherwise the time taken becomes longer.